Nadir creatinine in posterior urethral valves: How high is low enough?. Issue 6 (December 2015) - Coleman, R.; King, T.; Nicoara, C.-D.; Bader, M.; McCarthy, L.; Chandran, H.; Parashar, K.
Summary: Introduction: Large retrospective studies of people with posterior urethral valves (PUV) have reported chronic renal insufficiency (CRI) in up to one third of the participants and end-stage renal failure in up to one quarter of them. Nadir creatinine (lowest creatinine during the first year following diagnosis) is the recognised prognostic indicator for renal outcome in PUV, the most commonly used cut-off being 1 mg/dl (88.4 umol/l). Objective: To conduct a statistical analysis of nadir creatinine in PUV patients in order to identify the optimal cut-off level as a prognostic indicator for CRI. Study design: Patients treated by endoscopic valve ablation at the present institution between 1993 and 2004 were reviewed. Chronic renal insufficiency was defined as CKD2 or higher. Statistical methods included receiver operating characteristic (ROC) curve analysis, Fisher exact test and diagnostic utility tests. Statistical significance was defined as P < 0.05. Results and discussion: Nadir creatinine was identified in 96 patients. The median follow-up was 9.4 (IQR 7.0, 13.4) years. A total of 29 (30.2%) patients developed CRI, with nine (9.4%) reaching end-stage renal failure. On ROC analysis, Nadir creatinine was highly prognostic for future CRI, with an Area Under the Curve of 0.887 ( P < 0.001). Renal insufficiency occurred in all 10 (100%) patients with nadir creatinine >88.4 umol/l compared with 19 of 86 (22.2%) patients with lower nadir creatinine ( P < 0.001). As a test for future CRI, a nadir creatinine cut-off of 88.4 umol/l gave a specificity of 100%, but poor sensitivity of 34.5%. Lowering the cut-off to 75 umol/l resulted in improvement in all diagnostic utility tests (Table). All 14 (100%) patients with nadir creatinine >75 umol/l developed CRI, compared with 15 of 82 (18.3%) patients with lower nadir creatinine ( P < 0.001). Sensitivity only approached 95% at 35 umol/l, at which level specificity was low (Table). Two out of 36 (5.6%) patients with nadir creatinine <35 umol/l developed CRI. Multivariate analysis found recurrent UTI (OR 4.733; CI 1.297–17.280) and nadir creatinine >75 umol/l (OR 48.988; CI 4.9–490.11) to be independent risk factors for progression to CRI. Using cut-off values of 35 umol/l and 75 umol/l, patients can be stratified into low-, intermediate- and high-risk groups, with development of CRI in 5.3%, 28.3% and 100%, respectively ( P <0.001). The stage of CKD was higher in higher risk groups. Conclusion: Patients with nadir creatinine >75 umol/l (0.85 mg/dl) should be considered at high risk for CRI, while patients with nadir creatinine ≤35 umol/l (0.4 mg/dl) should be considered low risk. Patients with nadir creatinine between these two values have an intermediate risk of CRI. Table Diagnostic utility tests for identified nadir creatinine cut-off levels. Nadir creatinine cut-off (μmol/L) Sensitivity (%) Specificity (%) Positive predictive value (%) Negative predictive value (%) 88.4 34.5 100 100 78.8 75 48.3 100 100 81.7 35 93.1 50.7 45 94.4